1999
DOI: 10.1038/sj.bmt.1701993
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow transplantation for patients with Fanconi anemia: reduced doses of cyclophosphamide without irradiation as conditioning

Abstract: Summary:Fanconi anemia (FA), a rare autosomal recessive disease, frequently evolves to bone marrow failure and acute myeloid leukemia, and BMT is the treatment of choice for patients with FA. However, their exquisite hypersensitivity to DNA cross-linking agents is associated with severe complications and several investigators have been looking for the ideal preparatory regimen. We have been involved in a program of progressively decreasing doses of cyclophosphamide (CY) as conditioning therapy, in an attempt t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 15 publications
2
49
0
3
Order By: Relevance
“…[15][16][17][18] In FA, continuous improvements to the approach to BMT over the last 20 years have resulted in reduced regimen-related toxicity, superior engraftment and less GVHD, leading to improved survival. [19][20][21] However, in contrast to BMT with HLA-identical siblings, using alternate donors has been markedly less successful, due to the high rates of graft failure, regimen-related toxicity, GVHD and opportunistic infection. 20 For this purpose a more intensive conditioning with additional lowdose irradiation (IR) has been demonstrated to exert the immunosuppressive effect that enables durable engraftment.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] In FA, continuous improvements to the approach to BMT over the last 20 years have resulted in reduced regimen-related toxicity, superior engraftment and less GVHD, leading to improved survival. [19][20][21] However, in contrast to BMT with HLA-identical siblings, using alternate donors has been markedly less successful, due to the high rates of graft failure, regimen-related toxicity, GVHD and opportunistic infection. 20 For this purpose a more intensive conditioning with additional lowdose irradiation (IR) has been demonstrated to exert the immunosuppressive effect that enables durable engraftment.…”
Section: Introductionmentioning
confidence: 99%
“…7 In our experience, decreasing the doses of CFA without irradiation has resulted in lower rates of toxicity and acute and chronic GVHD, with good engraftment. [8][9][10] However, we have been limited to the setting of related transplantation.…”
Section: Jl Martímentioning
confidence: 99%
“…The frequencies of the traits can be as high as 3-9% for ␤ 0 thalassemia, and up to 54% or higher for Hb E. 1 Patients with ␤-thalassemia/Hb E can be as severely affected as those with homozygous ␤-thalassemia or Cooley's anemia. At present, allogeneic hematopoietic stem cell transplantation is the only curative therapy for thalassemia.…”
Section: Ayasmentioning
confidence: 99%
“…Medeiros et al 1 recently reported their results of allogeneic BMT in 16 patients with Fanconi's anemia (FA) using cyclophosphamide (CY) only as conditioning with a total dose of 100 mg/kg. One striking observation in this study is that no patient developed hemorrhagic cystitis.…”
mentioning
confidence: 99%